Mortality of chronic disorders of consciousness in adults and adolescents – a retrospective community based study from Salzburg, Austria - Schnetzer, Laura; Prüwasser, Tanja; Bergmann, Jürgen; Zimmermann, Georg; Kronbichler, Martin; Leis, Stefan; Trinka, Eugen (Frontiers in Neurology, 2024)
IntroductionEpidemiological data on disorders of consciousness (DoC) is rare and very heterogeneous due to difficulties in case ascertainment and differences in health care pathways between countries. This study reports data on mortality and survival time for DoC patients in Salzburg, Austria.MethodsAll patients with DoC were registered in the health care region of Salzburg North, Austria between 2007 and 2022 and their death data retrieved from the Statistik Austria. The 1- and 5-year mortality was calculated, also in relation to several explanatory variables (age, sex, etiology, diagnosis, CRS-R score, improvement). Furthermore, the incidence, survival functions using the Kaplan–Meier estimator and a Cox-Regression were calculated.ResultsThe mean annual incidence is 2.2 DoC/100.000 inhabitants in the Salzburg North region. The crude 1- and 5-year mortality rates were 25.9 and 55.1%, respectively, and the median survival of DoC patients based on the Kaplan–Meier estimator was 6.3 years. Moreover, the mortality was lower in women and in younger patients, those of traumatic etiology, and those with higher CRS-R scores, better diagnosis or an improvement of diagnosis until discharge from hospital.ConclusionThis article gives a rare insight into epidemiological data on DoC and shows which factors influence the mortality of these patients. Moreover, it is the first community based study on mortality of DoC in Salzburg, Austria.